Exploring active compounds of kelor (Moringa oleifera Lam.) leaves as an alternative medicine to improve immunity in facing COVID-19 via in silico study - Hikam, Agus Mohammad; Mubarakati, Nurul Jadid; Probojati, Rasyadan Taufiq; Widyananda, Muhammad Hermawan; Kharisma, Viol Dhea; Ansori, Arif Nur Muhammad (Genbinesia Journal of Biology, 2021)
SARS-CoV-2 is a new strain of coronavirus (CoV) that was identified in Wuhan in 2019. This virus is known to have the ability to reduce human immunity. Kelor (Moringa oleifera) is a potential natural resource in Indonesia, which is very abundant and contains several metabolic compounds such as phenolics, flavonoids, saponins, cytokines, and caffeoylquinic acid, which was reported to show antioxidants, antibacterial and antiviral. This study aims to predict the biological activity, physicochemical properties, toxicity, and affinity-interactions of the active compounds of M. oleifera leave. The active compounds of M. oleifera were obtained from the KNApSAcK and PubChem. Analysis of the bioactivity of the compounds using the Way2Drug Pass Online. Analysis of drug-likeness and toxicity using the Lipinski web server and pkCSM. Docking is done using Autodock vina software to analyze the interaction of the compounds with Mpro. The results indicate that the compound astragalin is the compound with the highest affinity value, namely -8.7 (kcal/mol), compared to lopinavir as a control compound with an affinity value -6.6 (kcal/mol). The types of bonds in astragalin compounds are hydrogen bonds with amino acids Glutamine 127 and Arginine 298. From these results, it is predicted that astragalin compounds have the highest potential as alternative drugs to increase body immunity against the COVID-19.